Emergent arboviruses in Brazil Arboviroses emergentes no Brasil - Luiz Tadeu Moraes Figueiredo (Revista da Sociedade Brasileira de Medicina Tropical, 2007)
Brazil is a large tropical country (8,514,215km²) with 185,360,000 inhabitants. More than one third of its territory is covered by tropical forests or other natural ecosystems. These provide ideal conditions for the existence of many arboviruses, which are maintained in a large variety of zoonotic cycles. The risk that new arboviruses might emerge in Brazil is related to the existence of large, densely populated cities that are infested by mosquitoes such as Culex and the highly anthropophilic Aedes aegypti. Infected humans or animals may come into these cities from ecological-epidemiological settings where arbovirus zoonoses occur. This study analyzes the risk of emergence of the alphaviruses Mayaro, Venezuelan equine encephalitis, Eastern equine encephalitis and Chikungunya; the flaviviruses yellow fever, Rocio, Saint Louis encephalitis and West Nile; and the orthobunyavirus Oropouche. O Brasil é país tropical de grande extensão territorial (8.514.215km²) e com 185.360.000 habitantes. Mais de 1/3 deste território é recoberto por florestas tropicais ou outros ecossistemas naturais com condições ideais para a ocorrência de diversas arboviroses as quais são mantidas em uma grande variedade de ciclos zoonóticos. O risco para a emergência de novos arbovirus no Brasil relaciona-se à existência de cidades grandes, populosas e infestadas por mosquitos Culex bem como o altamente antropofílico Aedes aegypti. Nas cidades poderiam ser introduzidos seres humanos ou animais infectados oriundos de sítios eco-epidemiológicos onde existem zoonoses arbovíricas. Neste trabalho, analisa-se o risco de emergência dos alphavirus Mayaro, da encefalite eqüina venezuelana, da encefalite eqüina do leste e Chikungunya, dos flavivirus, da febre amarela, Rocio, da encefalite de Saint Louis e do Nilo Ocidental, e do orthobunyavirus Oropouche.